Healthcare software design and implementation—A project failure case. (24th February 2020) - Ebad, Shouki A.
Summary: Electronic health records (EHRs) are implemented by many health care organizations as a potential service solution. Despite the appeal of EHRs, failure in their implementation can lead to negative consequences, ranging from the loss of money to reputation damage, for health care providers. However, the causes of this problem have not attracted the attention of a sufficient number of researchers. This paper aims to investigate this phenomenon objectively and subjectively in a public context using an interview‐based qualitative approach supported by archival data and records of a real‐world failed EHR project. The results show that the factors influencing failure are divergent and include technical and managerial issues. In particular, the timing and duration of the training as well as the integration of EHR with the enterprise systems were found to be the strongest influencing factors, followed by reasons related to the software design (eg, a lack of required pharmacy functionality) and software people management (eg, resistance to change). The paper also discusses points related to EHR development and design, such as the development paradigm, data quality and validation, architecture for security, and source code naming convention.